pH-STAT CALIBRATION FOR SESAME CAKE PROTEIN HYDROLYSIS BY ALCALASE - Demirhan, Elcin; Apar, Dilek Kilic; Ozbek, Belma (YILDIZ TECHNICAL UNIV, 2012)
In the present study, pH-stat method was calibrated by TNBS and OPA reactions for control of hydrolysis of sesame cake protein by Alcalase. Hydrolysis experiments were conducted in a batch reactor at the temperature of 50 degrees C for various pH values, and at pH 7.5 for the temperatures of 40 degrees C and 60 degrees C. The calibration was characterized by good linear correlations for both methods. The mean pK values of sesame cake protein hydrolysates were obtained as 6.88, 6.65 and 6.42 for 40, 50 and 60 degrees C, respectively.
Keywords: Sesame cake protein; hydrolysis; Alcalase; pH-stat; pK; Engineering